A highly stable and tightly packed 3D energetic coordination polymer assembled from nitrogen-rich tetrazole derivatives. (25th July 2018) - Zhang, Mi; Xu, Jian-Gang; Zhang, Ning-Ning; Lu, Jian; Xin, Xue-Huan; Zheng, Fa-Kun; Guo, Guo-Cong
Abstract : A tightly packed 3D energetic cadmium(ii ) coordination polymer was synthesized with high stability and remarkable energetic performance. Abstract : An energetic coordination polymer ([Cd(BTA)(H2 O)] n 1 (H2 BTA = N, N -bis(1(2) H -tetrazol-5-yl)-amine)) was solvothermally synthesized and structurally characterized. The structural analyses illustrate that compound1 exhibits a nonporous, tightly packed 3D PtS framework. Compared with the porous 3D metal–organic framework CoBTA (CoBTA = [Co9 (bta)10 (Hbta)2 (H2 O)10 ] n ), 1 displays higher density, better water resistance and thermal stability, and lower sensitivities. The enthalpy of formation of1 is 0.7519 kJ g −1, which is higher than that of the traditional explosive 2, 4, 6-trinitrotoluene (TNT, −0.2952 kJ g −1 ). The detonation velocity ( D ) and detonation pressure ( P ) of1 were calculated to be 6.283 km s −1 and 21.64 GPa, respectively. Sensitivity tests reveal that1 is insensitive to external stimuli. Based on the evaluation of energetic performance, 1 can act as an energetic candidate material with an approved level of safety.